Biomonitoring Studies in Geothermal Areas: A Review - Lattanzi, Pierfranco; Benesperi, Renato; Morelli, Guia; Rimondi, Valentina; Ruggieri, Giovanni (Frontiers in Environmental Science, 2020)
Biomonitoring is a widely employed approach to track changes in the environment. Its use to assess the impact of geothermal energy exploitation for power production is comparatively minor, and largely referred to Tuscany, Italy, geothermal fields. Most examples describe impacts on vegetation, particularly lichens. Biomonitoring proved useful as a tool to reveal the distribution of specific contaminants (e.g., mercury and H2S), and as an overall indicator of the impact on ecosystems. In consideration of the comparatively low cost/benefit ratio, the use of biomonitoring should be encouraged. In particular, it could prove useful to establish the natural background prior to development of geothermal exploitation, and to document any subsequent change.